2014
DOI: 10.1109/tia.2014.2346702
|View full text |Cite
|
Sign up to set email alerts
|

High-Resistance Grounded Power-System Equivalent Circuit Damage at the Line–Ground Fault Location—Part I

Abstract: This paper provides an electrical equivalent circuit of a high-resistance grounded (HRG) power supply transformer to discuss damage at a fault location so long as the fault remains a line-ground fault. Fault resistance and fault current that have an effect on damage are included in the equivalent circuit. Three-line diagrams showing fault current flows along with their vector diagrams are also included. Part II of this paper provides a similar equivalent circuit for an HRG grounded generator. This paper provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Hence, the symmetrical components of the transmission line impedance Z AB and the apparent reactive impedance of the FACTS device Z F ACT S are defined according to equation (20) as follows:…”
Section: Phase To Ground Fault Calculations In the Presence Of Facts mentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, the symmetrical components of the transmission line impedance Z AB and the apparent reactive impedance of the FACTS device Z F ACT S are defined according to equation (20) as follows:…”
Section: Phase To Ground Fault Calculations In the Presence Of Facts mentioning
confidence: 99%
“…More studies were conducted concerning the effect of fault location in distribution power systems, [10], unbalanced three-phase distribution systems, [11], transmission power system, [12], hybrid transmission lines, [13] and radial distribution systems with DG, [14]. Further studies addressed the effect of distributed generators on arcing faults, [15], current zero estimation technique to control the arcing time of circuit breakers, [16], bus-bar protection, [17], impedance fault protection in high voltage transmission lines, [18], groundfault feeder detection, [19], and an equivalent circuit of a high resistance grounded power supply transformer in the case of ground fault, [20]. With the growing stress on the aging existing grids, power systems face an unprecedented range of technical, economical, environmental and security challenges and constraints.…”
Section: Introductionmentioning
confidence: 99%
“…The choice of a particular safety factor is discussed in [9] and it is generally selected to be close to 1.25.…”
Section: A Ground Resistor Sizing and Pickup Settingsmentioning
confidence: 99%
“…Consequently, the authors believe that MSHA's present pickup setting of 40% of the NGR limit is appropriate. However, recent research of 4160 V systems has indicated that a pickup setting of 20% of the NGR limit for (4160-V systems) may be more appropriate for detecting arcing ground faults [9]. Therefore, this may be an area for future research for 15-kV class mine power systems.…”
Section: Ground Fault Pickup Settingmentioning
confidence: 99%
“…In medium voltage (MV) networks, HRG systems can limit the fault current to <10 A. These systems can also operate permanently during SLG faults [7,8]. Some other advantages of HRG systems are removing transient over-voltages and minimising electric shocks.…”
Section: Introductionmentioning
confidence: 99%